Sectoral approaches in electricity : building bridges to a safe climate - International Energy Agency (Paris : International Energy Agency, 2009)
Electricity accounts for more than 40 % of global energy-related CO2 emissions. This issue is most pressing for developing countries where growth in power demand is particularly high, fueling the risk of irreversible investment in CO2-intensive capacity, the so-called "carbon lock-in". -- Sectoral Approaches in Electricity – Building Bridges to a Safe Climate shows how the international climate policy framework could effectively support a transition towards low-CO2 electricity systems in developing countries. Sectoral approaches are intended to address sectors that require urgent actions, without waiting for countries to take nation-wide commitments. -- Earlier IEA publications have extensively reviewed developed countries’ efforts to steer generation away from carbon-intensive production modes, from dedicated support to low-carbon technologies to, increasingly, the reliance on CO2 pricing via emissions trading. Following the same logic, there are proposals seeking to use the international carbon market to drive changes at sectoral level in developing countries. This publication illustrates the pros and cons of such an approach in a few key emerging economies. It also asks how international climate policy could support and enhance ongoing efforts on end-use energy efficiency - an essential piece of the climate change/electricity puzzle.
Executive Summary -- Introduction -- 1. Tackling climate change in the electricity sector -- Emission trends and enery realities -- Climate change stabilisation and electricity -- The importance of demand-side efficiency improvements -- Summary -- 2. Presenting options for international sectoral approaches -- Electricity and climate in developing countries: lessons form the Clean Development Mechanism -- Proposed policy approaches beyond 2012 -- The rationale for sectoral approaches -- Sectoral approaches under the UNFCCC -- International sectoral initiatives and fora related to electricity -- Conclusion -- 3. Policy options to transform power generation -- Introduction -- A sobering message on crediting reductions in power generation -- Baselines for sector-wide crediting in power generation -- Triggering change with sectoral crediting: practical questions -- Sectoral crediting: an intermediary step -- 4 Targeting carbon lock-in: Casse studies on electricity -- Introduction and scope -- Electricity generation and consumption overview -- China -- India -- Mexico -- South Africa -- Stepping stones to curb CO2 from electricity -- 5. Next steps -- 6. References
Nad názvem: International Energy Agency
Obsahuje bibliografii
Keywords: International Energy Agency; elektrická energie; snižování emisí; oxid uhličitý; environmentální aspekty; klimatické změny; environmentální politika; rozvojové země; studie; electric power; air pollutant emission reduction; carbon dioxide; environmental aspects; climate changes; environmental policy; developing countries; studies